Accelerating target deconvolution for therapeutic antibody candidates using highly parallelized genome editing - Jenny Mattsson (Nature Portfolio, 2021)
Efficient deconvolution of antibody targets is needed for phenotype-based discovery. Here, the authors investigate a deconvolution approach based on pooled CRISPR Cas9 to achieve 97% deconvolution success rate.